Fibre optic interconnecting devices and passive components. Performance standard. Non-connectorized single-mode bidirectional 1490 / 1550 nm downstream and 1310 nm upstream WWDM devices for category O. Uncontrolled environment Part 086-6, (31st May 2011) - British Standards Institution,
No abstract available